National Partnership to Improve Dementia Care in Nursing Homes Campaign: State and Facility Strategies, Impact, and Antipsychotic Reduction Outcomes. Issue 3 (2nd June 2020) - Crystal, Stephen; Jarrín, Olga F; Rosenthal, Marsha; Hermida, Richard; Angell, Beth
Abstract: Background and Objectives: Antipsychotic medications have been widely used in nursing homes to manage behavioral and psychological symptoms of dementia, despite significantly increased mortality risk. Use grew rapidly during the 2000s, reaching 23.9% of residents by 2011. A national campaign for safer dementia care in U.S. nursing homes was launched in 2012, with public reporting of quality measures, increased regulatory scrutiny, and accompanying state and facility initiatives. By the second quarter of 2019, use had declined by 40.1% to 14.3%. We assessed the impact of state and facility initiatives during the Campaign aimed at encouraging more-judicious prescribing of antipsychotic medications. Research Design and Methods: Our mixed-methods strategy integrated administrative and clinical data analyses with state and facility case studies. Results: Results suggest that substantial change in prescribing is achievable through sustained, data-informed quality improvement initiatives integrating educational and regulatory interventions, supported by public quality reporting. Adequate staffing, particularly of registered nurses, is key to support individualized management of symptoms through nonpharmacological strategies. Case study results suggest that state and facility initiatives during the campaign achieved considerable buy-in for the goal of more conservative prescribing, through a social process of normalization. Reporting and reduction of antipsychotic use was not followed by increases in sedative-hypnotic medication use. Rather, sedative-hypnotic use declined in tandem with antipsychotic reduction, suggesting that increased attention to prescribing patterns led to more cautious use of other risky psychotropic medications. Discussion and Implications: Quality improvement initiatives to change entrenched but problematic clinical practices face many barriers to success, including provider-level inertia; perceptions that alternatives are not available; and family and staff resistance. Nevertheless, systemic change is possible through concerted, collaborative efforts that touch prescribing practices at multiple points; integrate educational and regulatory influences; activate local and state champions for improvement; foster reputational influences through public reporting and benchmarking; and support a social process of normalization of preferred care processes as a best practice that is in the interest of patients.